Environmental engineering : designing a sustainable future - Maczulak, Anne E. (Anne Elizabeth), 1954- (New York, NY : Facts on File, 2010)
From the Publisher: Green Technology is an eight-volume set that examines the relationship between human activities and their sometimes harmful consequences for the environment and explores new methods of repairing and restoring the Earth. Approaching environmental issues confronting society from a technological perspective has spawned significant controversy, and the books in this set present all sides of the debate. Designed to complement science curricula, the set also covers relevant history and new green technologies and innovations that will contribute to the field in the future. Environmental Engineering: Designing a Sustainable Future examines how this field, which incorporates not only aspects of art and design but also physics, geology, ecology, and the chemistry of matter, evolved from a discipline of civil engineering. Environmental engineers learn how to work with nature to improve and control the quality of the land, air, and water for the benefit of human and nonhuman cohabitation. Sidebars, figures, and case studies enhance fundamental concepts and examine urgent issues related to the'natural future' of the environment. The volume includes information on: aerodynamics; ecological and energy'architecture'; energy-efficient electronics; innovations in personal vehicles; landscape design; micro climates; solar homes; sustainable manufacturing; transit systems; and wastewater. The book contains 50 color photographs and line illustrations, five appendixes, a glossary, a detailed list of print and Internet resources, and an index. Green Technology is essential for high school students, teachers, and general readers who seek information on the important issues that affect the environment worldwide.
Includes bibliographical references (p. 194-203) and index.
Keywords: Environmental engineering; Environmental protection